Kredibilitas Dan Akurasi Virtualisasi Auditing Terhadap Kualitas Assesment Dan Opini Auditor - Firmansyah, Riski; Suhartini, Dwi; Sulistyowati, Erna (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to examine the credibility and accuracy of auditing conducted virtually on the quality of assessments and the resulting auditor opinions. This research analyzes directly with qualitative methods to determine the extent of the credibility and accuracy of virtual auditing on assessments and the resulting auditor opinions. Based on the results of interviews from direct practitioners with sufficient and professional experience, providing an understanding of virtual auditing in the modern era and automation in an in-depth and accurate manner. Overall, Virtual Audit has a positive impact on the quality of assessments and auditor opinions by increasing efficiency, objectivity, and transparency, although it also faces challenges that need to be overcome to ensure its successful implementation.